Granulomatous hypophysitis: experience with eight surgical cases of a single center. Issue 1 (December 2016) - Xu, Yan; Lou, Lin; Wang, Tian-Hua; Zhao, Yuan-Yuan; Cai, Xue-Xiang; Ma, Jie; Lu, Gang
Abstract Background Although primary hypophysitis is not uncommon, a granulomatous etiology of hypophysitis is relatively rare. Radiological and diagnostic characteristics of several isolated cases have been described to date. However, to the best of our knowledge, surgical treatment of eight cases of granulomatous hypophysitis confirmed by histopathology has not yet been reported. Methods A retrospective study was performed to review cases of granulomatous hypophysitis from November 2003 to November 2013 in our neurosurgical department. Only eight out of 1345 operations were diagnosed with granulomatous hypophysitis. Results The cohort included two men and six women. The most common manifestations reported were headache, fatigue and polyuria. All six female patients presented with either menstrual disorders or amenorrhea. Seven of eight patients suffered polyuria. Two patients suffered bitemporal hemianopsia. One was accompanied with eosinophilic granuloma of the skull. Prolactin levels were increased in six patients, four of them were noted to have thyroid axis imbalances, one was noted to be deficient in the gonadotropin axis and two were deficient in the adrenal axis. The lesion demonstrated homogenous enhancement and an abnormally thickened pituitary stalk. A histological diagnosis of granulomatous hypophysitis was established in all eight patients, who were treated surgically. Characteristic granulomas formed by epithelioid histiocytes and multinucleated giant cells were observed. Conclusion Pure glucocorticoid therapy is less effective than surgical intervention and has not been recommended for the treatment of granulomatous hypophysitis. Although replacement therapy can relieve associated symptoms, we conclude surgical intervention, particularly minimally invasive surgery via a transsphenoidal approach, to be mandatory in establishing a diagnosis and reducing the size of the inflammatory mass. Adjuvant corticosteroids therapy is recommended.